Utilização de instrumento de classificação de pacientes: análise da produção do conhecimento brasileira - Abreu, Sonia Portella de (2014)
The aim of the present study is to analyze the production of knowledge about the use of patient classification instruments in care and managerial nursing practice in Brazil. We conducted an integrative literature review, using the Latin American and Caribbean Center on Health Sciences Information (LILACS), Medical Literature Analysis and Retrieval Sistem on-line (MEDLINE) Cummulative Index to Nursing and Allied Health Literature (CINAHL) data bases for articles from January 2002 to December 2013. Data extracted from the articles were organized, categorized, and summarized using the Matrix method of literature review. The Research Appraisal Checklist (RAC) was used in order to evaluate the quality of the articles. Of the 1129 publications found, 31 met the selection criteria. The articles retrieved were classified into three categories according to the purpose of application: Assessment of Psychometric Properties, Patient Care Profile and Identification of Workload, and Planning Assistance. We found a higher number of articles in the category “patient care profile and workload” (n = 15) followed by the category “assessment of psychometric properties” (n = 14). According to RAC, 21 studies were appraised as superior studies and 10 studies were appraised as medium studies. We concluded that the Brazilian scientific production has not yet explored some purposes of using patient classification instruments in professional nursing practice. The identification of yet unexplored areas can guide future research on the topic.